2011
DOI: 10.1093/eurheartj/ehr372
|View full text |Cite
|
Sign up to set email alerts
|

Eight genetic loci associated with variation in lipoprotein-associated phospholipase A2 mass and activity and coronary heart disease: meta-analysis of genome-wide association studies from five community-based studies

Abstract: Levels of Lp-PLA2 mass and activity were associated with PLA2G7, the gene coding for this protein. Lipoprotein-associated phospholipase A2 activity was also strongly associated with genetic variants related to low-density lipoprotein cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 36 publications
5
87
1
Order By: Relevance
“…Lp-PLA 2 mass was found to be regulated mainly by PLA2G7 , consistent with another report ( 57 ). Lp-PLA 2 activity was strongly associated with genetic variants involved in lipid metabolism ( 56 ). The fi ndings of this interesting study suggest that genetic regions known to affect lipoprotein levels also infl uence Lp-PLA 2 expression.…”
Section: Biochemical and Structural Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…Lp-PLA 2 mass was found to be regulated mainly by PLA2G7 , consistent with another report ( 57 ). Lp-PLA 2 activity was strongly associated with genetic variants involved in lipid metabolism ( 56 ). The fi ndings of this interesting study suggest that genetic regions known to affect lipoprotein levels also infl uence Lp-PLA 2 expression.…”
Section: Biochemical and Structural Propertiessupporting
confidence: 90%
“…A recent genome-wide association study that included fi ve population-based reports comprising 13,664 subjects identifi ed eight genetic loci associated with variation in Lp-PLA 2 mass and activity ( 56 ). Lp-PLA 2 mass was found to be regulated mainly by PLA2G7 , consistent with another report ( 57 ).…”
Section: Biochemical and Structural Propertiessupporting
confidence: 69%
See 1 more Smart Citation
“…More recently, a genomewide meta-analysis of 13 664 participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE, which includes the FHS) Consortium identified genome-wide associations for the same variants, in addition to CETP for Lp-PLA 2 mass and PLA2G7 and LDLR for Lp-PLA 2 activity. 15 Variants in the loci identified through the FHS GWAS and the CHARGE meta-analysis are known to be involved in lipid metabolism and have been observed to strongly influence circulating levels of LDL-C and HDL-C.…”
Section: Clinical Perspective On P 685mentioning
confidence: 99%
“…23 But other studies on european Caucasians reported no association with CHd risk. 16,28 In south Koreans, a similar lack of association between A379V and CVd was reported. 19 personalized medicine is of growing interest, with a number of pharmacogenetic drug examples, like clopedogril and warfarin, where genetic variants influence the rate of drug metabolism and efficacy.…”
Section: Discussionmentioning
confidence: 62%